Enzymatic Conversion of Glucose to UDP-4-Keto-6-Deoxyglucose in Streptomyces spp. - Liu, Song Yu (American Society for Microbiology, 1998)
All of the 2,6-dideoxy sugars contained within the structure of chromomycin A(3) are derived from d-glucose. Enzyme assays were used to confirm the presence of hexokinase, phosphoglucomutase, UDPG pyrophosphorylase (UDPGP), and UDPG oxidoreductase (UDPGO), all of which are involved in the pathway of glucose activation and conversion into 2,6-dideoxyhexoses during chromomycin biosynthesis. Levels of the four enzymes in Streptomyces spp. cell extracts were correlated with the production of chromomycins. The pathway of sugar activation in Streptomyces spp. involves glucose 6-phosphorylation by hexokinase, isomerization to G-1-P catalyzed by phosphoglucomutase, synthesis of UDPG catalyzed by UDPGP, and formation of UDP-4-keto-6-deoxyglucose by UDPGO.